HBV evolution and genetic variability: impact on prevention, treatment and development of antivirals - Glebe, Dieter; Goldmann, Nora; Lauber, Chris; Seitz, Stefan (Antiviral research, 2021)
Hepatitis B virus (HBV) poses a major global health burden with 260 million people being chronically infected and 890,000 dying annually from complications in the course of the infection. HBV is a small enveloped virus with a reverse-transcribed DNA genome that infects hepatocytes and can cause acute and chronic infections of the liver. HBV is endemic in humans and apes representing the prototype member of the viral family Hepadnaviridae and can be divided into 10 genotypes. Hepadnaviruses have been found in all vertebrate classes and constitute an ancient viral family that descended from non-enveloped progenitors more than 360 million years ago. The de novo emergence of the envelope protein gene was accompanied with the liver-tropism and resulted in a tight virus-host association. The oldest HBV genomes so far have been isolated from human remains of the Bronze Age and the Neolithic (~7000 years before present). Despite the remarkable stability of the hepadnaviral genome over geological eras, HBV is able to rapidly evolve within an infected individual under pressure of the immune response or during antiviral treatment. Treatment with currently available antivirals blocking intracellular replication of HBV allows controlling of high viremia and improving liver health during long-term therapy of patients with chronic hepatitis B (CHB), but they are not sufficient to cure the disease. New therapy options that cover all HBV genotypes and emerging viral variants will have to be developed soon. In addition to the antiviral treatment of chronically infected patients, continued efforts to expand the global coverage of the currently available HBV vaccine will be one of the key factors for controlling the rising global spread of HBV. Certain improvements of the vaccine (e.g. inclusion of PreS domains) could counteract known problems such as low or no responsiveness of certain risk groups and waning anti-HBs titers leading to occult infections, especially with HBV genotypes E or F. But even with an optimal vaccine and a cure for hepatitis B, global eradication of HBV would be difficult to achieve because of an existing viral reservoir in primates and bats carrying closely related hepadnaviruses with zoonotic potential.
Gesehen am 12.08.2021
First published: 6 November 2020